En bättre mätmiljö : Standardisering och användaroptimering avmätsystem för motorprovcell - Ragnarsson, Albin (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2021)
This report is written as part of the thesis requirements for a bachelor of science in Automotive systems at Luleå University of Technology. BAE systems Hägglunds was in need of improved user interface and standardization of their test rigs for drivelines. There was a lack of a naming system for the sensors, formulas for efficiency and heating power as well as the absence of graphical view of the test objects with associated sensors. All of this is important for an efficient development procedure. Also a suggestion on suitable replacement of the mechanical water flow sensor was requested. This report presents the theory around the components and sensors regarding the test rigs, methods for making the decision and finished results. By developing an understanding of the test cell and test subjects, graphical recreations could be created with belonging calculations and documentation. Reading of analog signals and digital CAN-messages made it possible to collect and use the data from the sensors that was requested. By comparing the different flow sensors a of that the inductive flow sensor is most suitable for BAE System Hägglunds was made. The thesis resulted in a chosen naming system which is according to(Element)(Material)_(High/LowTemperature)_(Subject)_(In/Out). Formulas for efficiency and heating power, as well as 6 graphical views, 6 implemented views and 6 Excel documents was made and implemented in the DewesoftX software. The graphical views strongly improved the user interface of the test cell. Because some of the objects are classified they can also be used when presenting the data from testing without giving out more information than necessary. Also to make it easy to see where the sensors are placed and how to install the object in the test cell. This is very useful for BAE Systems Hägglunds that are now expanding their personal that will need basic knowledge of the test cell.